Recruiting, Retaining, and Graduating PhD Students: Practical Ideas From 73 Communication Sciences and Disorders PhD Program Coordinators. - Crais, Elizabeth; Lister, Jennifer; Tellis, Glen; Nunez, Loretta (Perspectives of the ASHA Special Interest Groups, 2018)
Given the documented shortage of PhD-level faculty to fill available Communication Sciences and Disorders Program openings, the American Speech-Language-Hearing Association Academic Affairs Board investigated models of PhD education in Communication Sciences and Disorders Programs. The American Speech-Language-Hearing Association Academic Affairs Board members conducted interviews with 73/76 PhD program coordinators from institutions in Communication Sciences and Disorders Programs. The current article highlights the responses from those interviews and provides recommendations that can be used by PhD programs to examine their own practices and policies in PhD education.